Quercetin Improves Glucose and Lipid Metabolism of Diabetic Rats: Involvement of Akt Signaling and SIRT1. (12th December 2017) - Peng, Jing; Li, Qingde; Li, Keye; Zhu, Li; Lin, Xiaoding; Lin, Xiaohong; Shen, Qianhui; Li, Guoping; Xie, Xi
Abstract : Glucose and lipid metabolism disorder in diabetes mellitus often causes damage to multiple tissues and organs. Diabetes mellitus is beneficially affected by quercetin. However, its concrete mechanisms are yet to be fully elucidated. In our study, diabetes was induced in Sprague-Dawley rats by STZ injection. The rats were randomly divided into normal control, diabetic model, low-dose quercetin treatment, high-dose quercetin treatment, and pioglitazone treatment groups. Fasting blood glucose was collected to evaluate diabetes. Immunohistochemistry and fluorometric assay were performed to explore SIRT1. Akt levels were measured through immunoprecipitation and Western blot. After 12 weeks of quercetin treatment, the biochemical parameters of glucose and lipid metabolism improved to varying degrees. Hepatic histomorphological injury was alleviated, and hepatic glycogen content was increased. The expression and activity of hepatic SIRT1 were enhanced, and Akt was activated by phosphorylation and deacetylation. These results suggested that the beneficial effects of quercetin on glucose and lipid metabolism disorder are probably associated with the upregulated activity and protein level of SIRT1 and its influence on Akt signaling pathway. Hence, quercetin shows potential for the treatment of glucose and lipid metabolism disorder in diabetes mellitus.